A critique of Botswana's language policy from a translanguaging perspective. Issue 2 (3rd April 2017) - Bagwasi, Mompoloki Mmangaka
ABSTRACT: This paper critiques the language practices and language-in-education policy of Botswana from a translanguaging perspective. By so doing, it revisits our commonly held perceptions about multilingualism, bilingualism and language and its boundary. We commonly perceive languages as autonomous and as having boundaries and we perceive bilingualism or multilingualism as consisting of two or more of these fixed languages. Such views have come under attack by theorists who, after observing the movements of people and languages as well as the language practices of bilinguals, have come to the conclusion that languages can neither be separated nor fixed to any one speech community, location or function. The current paper finds weakness in Botswana's approach to language planning and language-in-education policy. It argues that the approach does not promote multilingualism, that it is out of touch, and prescriptive in so far as it fails to recognize that multilingualism is supposed to embrace flexibility, continuity and multiplicity. The paper advocates for the translanguaging approach which appreciates the fuzziness of language boundaries, the fluidity and creativity of languages instead of their distinctiveness. The paper recommends a language-in-education policy which is akin to what bilinguals do in their speech and conversations, that is, a language policy that allows for the use of several languages in the classroom and enables learners to utilize their whole linguistic repertoire to interrogate issues, understand the subject matter and express themselves fully.